Writing from sources - Spatt, Brenda (St. Martin’s Press, 1991)
Writing from Sources provides students with a complete guide to the skills of doing research and integrating the results confidently and effectively into their own prose, while providing instructors with all the readings and prompts they need for a complete course in source-based writing. To teach students a reliable process for working with sources, the book builds systematically from simpler skills such as finding a topic and looking for sources to more demanding ones such as choosing appropriate sources and integrating them smoothly with the writer's own ideas, providing detailed guidance and examples for each step. Many exercises and writing assignments, supported by numerous readings ranging from brief excerpts to full essays, provide ample practice in every skill.